Pelatihan Pengolahan Administrasi Data Desa untuk Mewujudkan CANTIK (Cinta Statistika) bagi Perangkat Desa di Kantor Desa Kerik Kecamatan Takeran - Lusiana, Restu; Murtafiah, Wasilatul; Suprapto, Edy; Apriandi, Davi; Krisdiana, Ika; Setyansah, Reza Kusuma (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
In the era of digitalization, developing village officials requires human resources who can adapt to technology. This is closely related to the demand generated by the Covid-19 pandemic, where all activities are conducted online and physical gatherings are prohibited. This is necessary to ensure that village officials' skills continuously improve and they become proficient in operating electronic devices, particularly computers. The training is intended to equip all village officials in Kerik sub-district Takeran Magetan district with the skills to manage village data administration using statistical data and create infographics, based on the service requirements. The primary goals of this training are managing village archive data, financial management, and population statistics. This training delivers both theoretical and practical components. Hence, the Mathematics Education Study Program at PGRI Madiun University organised a training session at Kerik Village Office, Takeran District. This session aimed to train Village Officials in processing village data administration using Google Spreadsheet with a focus on Love Statistics (CANTIK concept). This training session utilises Google Spreadsheet to teach basic operational skills with the help of descriptive statistics. The training covers five parts that include an introductory session on Google Spreadsheet, Ribbon parts and functions, data management, data analysis, and data printing. The training session was carried out smoothly, and its success was measured by the enthusiasm of the participants during the training, as well as the post-activity evaluation and monitoring. The participants are now competent in managing the village office data properly as they work.